Services-oriented learning commons model for public libraries - Mondejar, Liafeil C. (2016)
The never ending advances and changes both in technology and learning methods prompted the development of a new library model more commonly known as Learning Commons for academic libraries and school libraries. The implementation of this new model revitalized the libraries, increasing their relevance and solidifying its role within the academic community. This study sought to determine the feasibility of applying this model in public libraries to help strengthen its relevance to its community. A model containing five fundamental characteristics for the academic library Learning Commons was used as basis for this study. Each characteristic is composed of elements defining the model. This model was tested in terms of applicability to public libraries through the employment of a survey. Forty respondents from five city public libraries in Metro Manila rated each element according to the degree of its relevance and applicability to the public library.